Rekonstruksi Kebijakan Penertiban Tanah Terlantar di Wilayah Indonesia Perspektif Teori Hukum Tanah dan Etika Lingkungan - Putra, Ida Bagus Dwi Cahyadi; Dananjaya, Nyoman Satyayudha (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024)DO - 10.24843/AC.2024.v09.i01.p2, 2024)
The purpose of this study is to analyze the rules for the policy of controlling abandoned land in guaranteeing legal certainty for land objects indicated in controlling abandoned land, as well as assessing the legal position of those who have the right of the land who have the potential to suffer losses as a result of being targeted for controlling abandoned land. This research is a normative research with a statute approach, a conceptual approach, and a case approach, as well as supported by data collection techniques with a card system. The results in this study are the need for a reconstruction of norms to reinforce the elements of designating abandoned land, so that with the existence of regulations regarding controlling abandoned land by the government will change the abandoned status. The protection of land rights for both individuals and legal entities whose land is designated as abandoned land granting compensation for the land which re-ocoupied by the state. Regarding the provision of compensation for the land, is regulated in Government Regulation Number 41 of 1964 concerning Amendments and Supplements to Government Regulation Number 224 of 1961 concerning Implementation of Land Distribution and Provision of Compensation.